Synergistic Collaboration of Pharmacists and Nurses in Enhancing Patient Care (Asian Journal of Pharmaceutics (AJP), 2024)
Collaboration between pharmacists and nurses is widely seen as an important synergistic collaboration inenhancing patient care by addressing issues such as drug mistakes, growing healthcare expenditures, andcomplex illness management. Their combined expertise enhances patient care by optimizing drug therapy,improving patient education, and reducing preventable medication-related issues. This article reflects thesynergistic collaboration of pharmacists and nurses in enhancing patient care. A literature analysis was doneto investigate research on multidisciplinary interaction between pharmacists and nurses in diverse healthcaresettings, with an emphasis on their roles in drug management, patient education, and therapy optimization toreduce any avoidable interactions. Collaboration dramatically lowers medication mistakes, increases patientadherence, and improves overall clinical results, including chronic disease management. Despite the benefits,communication gaps and ambiguous responsibilities hinder successful synergistic collaboration. Addressingthese hurdles through improved training and integration of certain healthcare systems software for bettercollaboration is critical to maximize the advantages of this collaborative effort. Pharmacist-nurse collaborationimproves patient care and safety, and overcoming current obstacles can lead to more efficient, patient-centeredhealthcare systems. Despite the great perks of collaboration, there are certain obstacles to smooth collaborations.These obstacles can be addressed by providing proper training and integration of AI and other technical softwarefor a smooth collaboration. With the partnership between pharmacists and nurses, much scope will be realizedto improve patient-centered care. The removal of present obstacles and incitement of closer collaboration willmake it possible for healthcare systems to improve clinical results, lower prescription errors, and guarantee moreeffective and patient-focused care delivery.